IMPLEMENTASI PROGRAM BOARDING SCHOOL DALAM PEMBENTUKAN KARAKTER SISWA DI SMA NEGERI CAHAYA MADANI BANTEN BOARDING SCHOOL PANDEGLANG - Najihaturrohmah, Najihaturrohmah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2017)
This study aims to determine the implementation of boarding school programs in the formation of student characters in State Senior High School of Cahaya Madani Banten Boarding School Pandeglang Banten. The type of this research is qualitative descriptive research. The research data was collected with several techniques, such as observation, interview, and documentation. Triangulation technique is done by means of triangulation method, that is by checking the information result of interview with documentation and observation. The results of the discussion of the implementation of boarding school programs in the formation of student characters include: There is guidance of character education that appear in State Senior High School of Cahaya Madani Banten Boarding School Pandeglang Banten include: 1) Religious, attitude, and behavior; 2) Discipline, actions that demonstrate orderly conduct and abide by various rules and regulations. 3) Honest behavior based on an attempt to make himself or herself a person who can always be trusted in words, actions, and work. 4) Mandiri, 5) Responsibility of the attitude and behavior of a person to carry out his duties and obligations, which he should do, to oneself, society, environment (nature, social and culture), state, and god almighty. Keywords. Boarding school, character education, religious, discipline